Kesalahan Siswa pada Soal Cerita Fungsi Kuadrat Berdasarkan Teori Nolting - Islamiyah, Wafa; Suryadi, Didi; Gulvara, M Akbar (Edumatica : Jurnal Pendidikan Matematika, 2023)
This research aims to describe students' errors in solving story problems related to quadratic functions and identify the underlying factors causing these errors. The research conducted is qualitative. The study took place in one of the junior high schools in South Kalimantan, involving 5 subjects from Grade IX. The research instrument used was three descriptive story problems—data collection techniques involved analyzing the answers to the descriptive test and conducting interviews. Based on the analysis, the types of errors made by the subject are as follows: 1) Misread-direction errors (30%): Students failed to read the instructions properly due to rushing or being unfamiliar with reading question instructions. 2) Careless errors (40%): Students made calculation mistakes due to lack of attention to detail. 3) Concept errors (20%): Students lacked understanding of quadratic function concepts due to insufficient study. 4) Application errors (33.33%): Students could not apply concepts and formulas effectively in solving problems due to a lack of comprehension of the subject matter. 5) Test-taking errors (66.67%): Students failed to restate information from the problem because of being in a hurry and unfamiliar with solving story problems.